Logika Kepantasan di Sangihe-Talaud: Kerjasama Indonesia-Amerika Serikat dalam INDEX-SATAL - Feliatra, Kevin Rafif; Basith Dir, Andi Akhmad (Journal of International Relations, 2020)
INDEX-SATAL (Indonesian Exploration–Sangihe-Talaud Expeditions) is a cooperation led by the United States to explore Sangihe-Talaud, region in Indonesia, which is very rich in deep sea’s natural resources. This collaboration is a form of Marine Scientific Research. The main problem in this issue is that the US has a bad reputation in international sea regime and historically had eroded the wealth of Indonesian mines. This research then discuss why Indonesia continues to accept United States despite these risks. This research uses the perspective of the Logic of Appropriateness, which explains that state will do something that fulfills moral obligations that come from such situations, identity, role, and membership in political community. The research method is explanative by using literature reviews. The result show that the US was accepted by Indonesia due to the alignment of situation and Indonesia’s identity, the role of Indonesia as UNCLOS’ ratified country, and Indonesia’s moral responsibility as a maritime nation.